Efecto de los análogos de las hormonas liberadoras de gonadotropinas (Buserelina) y de la prostaglandina f2α (Cloprostenol), en la activación del celo y la fertilidad en vacas lecheras - provincia de Lamas - San Martín - Vela Huanca, Esther Maria (2016)
The hormonal interventions have been used to improve the probability of detection of zeal and Artificial Insemination thus improving the rates of pregnancy in dairy animals in different management systems. The objective of this research work is to contribute to the development of programs that allow a management of the reproductive cycles in dairy cows in the tropics. The study focused on the effect of the synthetic analogues of gonadotropin-releasing hormone (buserelin) and prostaglandin f2α (Cloprostenol), single and joint, on activation of the zeal and the rate of fertility in dairy cows. We evaluated 48 dairy cows in four groups treated, as we detailed: T0: witness (12 cows); T1: buserelin (12 cows), T2: Cloprostenol (12 cows), T3: buserelin plus Cloprostenol (12 cows). We made the selection of cows by rectal palpation to diagnose that were not pregnant and to submit cyclicality ovarian with presence of follicles in growth or with the corpus luteum. We made the application of hormones according to the Protocol established, in T1 and T2 expected that the cow manifest sign of estrus to be inseminated, in the T3 IATF. The diagnosis of pregnancy was made by rectal palpation from day 60 after the artificial insemination